Electrochemical, theoretical and surface physicochemical studies of the alkaline copper corrosion inhibition by newly synthesized molecular complexes of benzenediamine and tetraamine with π acceptor - Ibrahim, Mohamed M.; Mersal, Gaber A. M.; Fallatah, Ahmed M.; Saracoglu, Murat; Kandemirli, Fatma; Alharthi, Sarah; Szunerits, Sabine; Boukherroub, Rabah; Ryl, Jacek; Amin, Mohammed A. (Elsevier BV, 2020)
Abstract Two charge transfer complexes, namely [(BDAH)+(PA−)] CT1 [(BTAH)2+(PA−)2] and CT2 (BDAH = 1,2-benzenediamine, BTAH = 1,2,4,5-benzenetetramine, and PA− = 2,4,6-trinitrophenolate), were synthesized and fully characterized using various spectroscopic techniques. CT1 and CT2 were tested as inhibitors to effectively control the uniform and anodic corrosion processes of copper in an alkaline electrolyte (1.0 M KOH) using various electrochemical techniques. As a reference point, results were compared with the potassium salt of the π-acceptor potassium 2,4,6-trinitrophenolate (designated here as PA−K+). The highest inhibition efficiency (97%) was recorded for inhibitor CT2 at a concentration of 1.0 mM. The inhibition mechanism was discussed based on scanning electron microscopy and X-ray photoelectron spectroscopy results of the corroded and inhibited Cu surfaces. A theoretical study, based on quantum-chemical calculations of the synthesized compounds, performed by the DFT/B3LYP method with a 6-311++G(2d,2p) basis set by using Gaussian 09, Revision A.02 program, was also included to support experimental findings. The various quantum chemical parameters such as EHOMO, ELUMO, chemical hardness, and chemical softness of the investigated molecules were calculated, and their correlation with the inhibition efficiency of the synthesized compounds was discussed.
Keywords: B3LYP; [SPI] Engineering Sciences [physics]; Single crystal; Alkaline corrosion; DFT; Corrosion inhibitor; Quantum chemical calculation; Charge transfer complexes; Copper; 3. Good health